2008
DOI: 10.1177/1533317507310570
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dementia in an Urban Turkish Population

Abstract: A cross-sectional, population-based, 2-stage prevalence study was conducted in a sample of 1019 community-dwelling persons over the age of 70 years living in Istanbul. In the first phase, participants were screened with the Mini-Mental State Examination for evidence of cognitive impairment. In the second phase, 79% of those who screened positive (n = 322) and 9% of screen-negatives (n = 63) underwent a standardized diagnostic workup. Diagnosis of dementia and Alzheimer's disease (AD) was made according to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 47 publications
4
57
1
9
Order By: Relevance
“…Although mean MMSE score was found to be 26.2 and the frequency of CImp was 26.1% in comparison of the distribution of CImp between certain age groups, the odds ratio of CImp after 75 years was higher than that between 60 and 64 years ( Table 2). CImp risk increases with age and it is more prevalent in females compared with males (1,19,20,25,(33)(34)(35). Our results confirm this finding from other studies, and although the rate of CImp in females is similar, prevalence of CImp in our study is higher than other studies in both sexes (males: 20.6%, females: 31.5%).…”
Section: Discussionsupporting
confidence: 86%
“…Although mean MMSE score was found to be 26.2 and the frequency of CImp was 26.1% in comparison of the distribution of CImp between certain age groups, the odds ratio of CImp after 75 years was higher than that between 60 and 64 years ( Table 2). CImp risk increases with age and it is more prevalent in females compared with males (1,19,20,25,(33)(34)(35). Our results confirm this finding from other studies, and although the rate of CImp in females is similar, prevalence of CImp in our study is higher than other studies in both sexes (males: 20.6%, females: 31.5%).…”
Section: Discussionsupporting
confidence: 86%
“…In 2003, Cankurtaran et al (15) identified that from a total of 1255 elderly, 14.4% had dementia. Gurvit et al (16) reported that the prevalence of dementia in people aged >70 years living in İstanbul was 20%. The worldwide incidence of dementia in people aged >65 years is 10%-15%, and it is 30%-50% in people aged >80 years (17).…”
Section: Discussionmentioning
confidence: 99%
“…Türkiye'de ve dünyada çok sayıda genel populasyonda demans prevelansını ortaya koyan çalışmalar yapılmıştır. Bu çalışmalara göre genel populasyonda demans sıklığı %2.4 ten %22.9'a kadar değişmektedir (14)(15)(16)(17). Ülkemiz doğu bölgesinde Bulut ve arkadaşlarının yaptığı saha çalışmasında 65 yaş üstü kişilerde bilişsel yetmezlik oranının %10 olduğu ortaya çıkmıştır (18).…”
Section: Discussionunclassified